Pipistrellus kuhlii ... - Honacki, James H.; Kinman, Kenneth E.; Koeppl, James W. (Zenodo, 1982)
Pipistrellus kuhlii (Natterer, 1819). In Kuhl, Ann. Wetterau Ges. Naturk., 4(2): 199. TYPE LOCALITY: Italy, Friuli-Venezia Giulia, Trieste. DISTRIBUTION: S. Europe through the Caucasus to Kazakhstan and Pakistan; S.W. Asia; most of Africa. ISIS NUMBER: 5301405014019024001 as P. kuhli (sic). ... : Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Chiroptera, pp. 111-215 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 198, DOI: 10.5281/zenodo.7352990 ...